2015
DOI: 10.14210/alcance.v22n1.p173-190
|View full text |Cite
|
Sign up to set email alerts
|

Arrumar Devagarzinho Os “Trem”, Puxar Carroças, Bingar Bicicleta, Engajar Pessoas: A Difícil Arte De Criar E Gerir Uma Associação De Catadores De Recicláveis

Abstract: RESUMOObjetiva-se fomentar discussões e reflexões sobre a criação e o gerenciamento de uma associação, com vistas ao engajamento das pessoas na lógica associativista. Pode ser usado em disciplinas que abordem o Empreendedorismo Social, a Responsabilidade Socioambiental e a Gestão nos cursos de graduação e pós-graduação. É narrada a história de um grupo de catadores de materiais recicláveis que moravam em uma favela em Goiânia, Goiás. Muitas dificuldades foram enfrentadas pelos catadores, como as condições prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Austin et al (2012), regarding the obstacles faced by social entrepreneurs, mention the following situations: limited access to best talents, little funding, limited tools and resources and strategic rigidity, which hinder the ability to mobilize resources. With poor working and housing conditionswhich is the case of the waste pickers analyzed in our research and in other studies (Freitag et al, 2015) social entrepreneurs present growth intentions, but they are aware that, in order to grow, it is necessary to obtain higher volumes of inputs, more machinery and more resources to expand activities. According, to Freitag et al (2015), the difficulties observed by the authors interfered in the search for empowerment because many pickers believed that the individual collection of waste presented more advantages.…”
Section: Strategymentioning
confidence: 69%
See 1 more Smart Citation
“…Austin et al (2012), regarding the obstacles faced by social entrepreneurs, mention the following situations: limited access to best talents, little funding, limited tools and resources and strategic rigidity, which hinder the ability to mobilize resources. With poor working and housing conditionswhich is the case of the waste pickers analyzed in our research and in other studies (Freitag et al, 2015) social entrepreneurs present growth intentions, but they are aware that, in order to grow, it is necessary to obtain higher volumes of inputs, more machinery and more resources to expand activities. According, to Freitag et al (2015), the difficulties observed by the authors interfered in the search for empowerment because many pickers believed that the individual collection of waste presented more advantages.…”
Section: Strategymentioning
confidence: 69%
“…Considering they rely on few resources, social and solidarity enterprises face several difficulties in the market, such as the lack of legitimacy, visibility (Corrêa & Teixeira, 2015;Freitag, Camargo Filho, Borges de Carvalho & Borges, 2015;Gaiger, 2015;Nicolopoulou, 2014) and qualification (God oi-de-Sousa, Nakata & Caladão 2014). Besides, the shortage of resources contributes to the low confidence of these entrepreneurs (Nicolopoulou, 2014;Urbano, Toledano & Toriano, 2010), which may affect venture growth.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, Gutberlet et al (2016), ao realizarem uma pesquisa com catadores cooperados na região metropolitana de São Paulo, relatam que a falta de acesso à água e a banheiros desses trabalhadores durante sua longa jornada de trabalho reforça o argumento de condições de trabalho insalubres. Freitag et al (2015), ao trazerem relatos de associados de uma Associação de Catadores em Goiânia, apresentam que um dos desejos desses cidadãos é um banheiro no local de trabalho. Também em Goiânia, Guimarães (2018) estudou questões de direitos humanos no universo da catação de recicláveis e relata a precariedade de banheiros de uma das cooperativas estudadas, apesar de estarem limpos.…”
Section: Dhas Em Esferas Da Vida Além Do Domicíliounclassified